1987
DOI: 10.1016/s0735-1097(87)80158-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular abnormalities accompanying acute spinal cord injury in humans: Incidence, time course and severity

Abstract: The frequency of cardiovascular abnormalities was evaluated in 71 consecutive patients with acute injury to the spinal cord. Persistent bradycardia was universal in all 31 patients with severe cervical cord injury and less common in milder cervical injury (6 of 17) or thoracolumbar injury (3 of 23) (p less than 0.00001). Marked sinus slowing (71 versus 12 versus 4%, respectively, p less than 0.00001), hypotension (68 versus 0 versus 0%, p less than 0.00001), supraventricular arrhythmias (19 versus 6 versus 0%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
0
8

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(188 citation statements)
references
References 25 publications
6
174
0
8
Order By: Relevance
“…Also, the risk of dysrhythmia and valvular disease was similarly higher in those with more complete and more rostral SCIs. A propensity toward dysrhythmias has been documented acutely after SCI, 24 though it has not been shown that chronic SCI is associated with dysrhythmia in the absence of underlying CHD. 25 While dysrhythmia could be associated with heightened cerebrovascular disease risk, the reason why valvular disease is elevated according to level and Frankel/ASIA grade is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the risk of dysrhythmia and valvular disease was similarly higher in those with more complete and more rostral SCIs. A propensity toward dysrhythmias has been documented acutely after SCI, 24 though it has not been shown that chronic SCI is associated with dysrhythmia in the absence of underlying CHD. 25 While dysrhythmia could be associated with heightened cerebrovascular disease risk, the reason why valvular disease is elevated according to level and Frankel/ASIA grade is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…9 Despite the theoretical basis for increased incidence of cardiac dysrhythmia in the SCI population, this did not appear to be clinic ally significant. Furthermore, clinical follow up of the SCI population in this study was unable to demonstrate the presence of any clinical events associated with cardiac dys rhythmia in this population for a 2-year follow up period after Holter monitoring.…”
Section: Referencesmentioning
confidence: 98%
“…8 From the cardiological perspective, acute SCI patients experience an alteration in cardiac and hemodynamic status related to injury induced autonomic nervous system dysfunction. 9 Cardiac dysrhythmias are a particular concern in the acute phases of SCI (less than 14 days of injury). Ubiquitous episodes of persistent bradycardia in patients with cerv ical SCI have been demonstrated but are rarely noted in SCI patients experiencing thoracolumbar levels of injury.…”
Section: Introductionmentioning
confidence: 99%
“…80 Reports from acute care settings show that vasovagal hypotension and bradyarrhythmias resolve in 3-6 weeks. 81,82 Orthostatic hypotension as a result of standing a tetraplegia subject, however, may persist for 10-12 weeks or longer. 83 In contrast, the malignant hypertension of autonomic dysreflexia develops by weeks to months and persists indefinitely.…”
Section: Clinical Descriptionmentioning
confidence: 99%